Millar Susan interview - (:unkn) unknown (My University, 2010)
Dr. Susan Millar is the Director of Education Research at the Morgridge Institute for Research. This interview discusses her role in the early conceptualization and development of the Wisconsin Institutes for Discovery. The audio recording of this interview is withheld at the request of the participant.